Preclinical Investigations with Mistletoe (Viscum album L.) Extract Iscador - Maldacker, Juliane (Arzneimittelforschung, 2006)
The mistletoe (Viscum album L.) extract Iscador® has been shown to be an effective complementary drug in the treatment of cancer patients after surgical removal of the primary tumor. It improved survival, recovery from damage caused by irradiation or cytostatic therapy, and quality of life. Beneficial effects were seen especially as reduction of the side effects caused by basic oncological therapy. In animal tests, clear anti-carcinogenic effects of Iscador were demonstrated as reduction of tumor growth in preformed tumors and as prevention of tumor growth in newly induced tumors. Mainly immune stimulation but also direct cytotoxic activity are believed to be responsible for the anti-carcinogenic activity of Iscador. Other effects seen in patients, such as improved quality of life and improved psychic conditions, are not possible to be tested in animals.Recently, toxicological investigations were performed with Iscador to get more information on possible toxicological effects which can only be evaluated in preclinical studies. Tests examining the acute toxicity, genotoxic effects as well as effects on reproduction were performed. In these studies, no adverse effects of Iscador preparations were detected thus confirming the information on the safety of the extract which has been gained in clinical trials and during more than 80 years of use in human therapy. Iscador has been shown to be essentially safe. No severe adverse events have been reported during many years of use by thousands of patients. Genotoxic effects and effects on reproduction, which cannot be evaluated in clinical use, have been cleared up in animal tests. Iscador was shown to be clearly non-genotoxic and free of relevant toxic effects on reproduction in vivo. In summary, no risk of adverse effects of Iscador during human use is expected.
Keywords: Iscador®; Mistletoe extract, anti-tumor activity, preclinical investigations, toxicological investigations; Viscum album L.